KEARIFAN LOKAL SUKU MANDAR “MEPUANG DAN METABE” TERHADAP PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR DI KABUPATEN POLEWALI MANDAR - Paida, Andi; Candra, Candra; Asriati, Asriati; Indrawaty, Indrawaty; Sriwahyuni, Sriwahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Indonesia is rich in diverse culture and local wisdom, one of which is the Mandar tribe tradition in Polewali Mandar Regency, West Sulawesi. This local wisdom plays an important role in forming the character of individuals and society. The